Enzymatic Synthesis of Palm Based Fatty Monoethanolamide - Abdul Rahim, Rashidah (2002)
Fatty monoethanolamides, derived from a reaction between triglyceride, palm kernel olein (PKL) or free fatty acids and primary amine alcohol, monoethanolamine (MEA) can be synthesised enzymatically, under milder conditions than the energy intensive chemical reaction. Mixture of palm based fatty monoethanolamide was successfully obtained from the reaction between PKL and MEA in the presence of enzyme with better yield than the control experiment (without enzyme). The various individual fatty monoethanolamides were also obtained from the reaction between free fatty acids (ClOCIS) and MEA after the isolation and purification processes. The various fatty monoethanolamides were used as standards for the analysis of product mixture. Fatty monoethanolamides were characterised by infra-red spectroscopy (IR), thin-layer chromatography (TLC), nuclear magnetic resonance (NMR) and gas chromatography (GC). Gas chromatograph was also used for the quantitative analysis to calculate percent yield by using internal standard method.